Greek gynecology healthcare professionals towards quality management systems. Issue 1 (11th February 2019) - Dinas, Konstantinos; Vavoulidis, Eleftherios; Pratilas, Georgios Chrysostomos; Basonidis, Alexandros; Liberis, Anastasios; Zepiridis, Leonidas; Sotiriadis, Alexandros; Papaevangeliou, Dimitra; Stathopoulou, Aliki; Leimoni, Eirini; Pantazis, Konstantinos; Tziomalos, Konstantinos; et al.
Abstract : Purpose: Today, quality management systems (QMS) are a promising candidate for the improvement of healthcare services. The purpose of this paper is to investigate the opinions/attitudes of gynecology healthcare professionals toward quality and quality management in healthcare facilities (HFs) in Greece. Design/methodology/approach: An anonymous self-administered questionnaire was distributed to healthcare professionals, asking for opinions on quality objectives associated with the everyday workflow in HFs (e.g. management of patients, resources, etc.) and on QMS. The study was conducted in Hippokration Hospital of Thessaloniki, including 187 participants. Statistical assessment and analysis of the questionnaires were carried out. Findings: Although 87.5 percent recognized the importance of potential QMS implementation and accreditation, over 50 percent believed that it would lead rather to increased workload and bureaucracy than to any considerable quality improvement. More than 60 percent were completely unaware of the implementation of quality objectives such as quality handbook, quality policy, audit meetings and accreditation status in their HFs. This unawareness was also reported in terms of patient, data, human and general resources management. Finally, awareness over medical malpractice and positive attitude toward official reporting were detected. Originality/value: Most respondents acknowledged the significance of quality, QMS implementation and accreditation in Greek hospitals. However, there was a critical gap in knowledge about quality management objectives/processes that could be possibly resolved by expert teams and well-organized educational programs aiming to educate personnel regarding the various quality objectives in Greek HFs.